A novel frequency-free movable test vehicle for retrieving modal parameters of bridges: Theory and experiment. (1st May 2022) - Yang, Y.B.; Li, Z.; Wang, Z.L.; Shi, K.; Xu, H.; Qiu, F.Q.; Zhu, J.F.
Highlights: Propose firstly a novel frequency-free movable test vehicle for retrieving bridge modal parameters. Use PU tires to make the test vehicle, which does not show frequency up to 20 Hz. Using the test vehicle in parked state eliminates the pavement roughness effect. By applying to multi-span bridges, the proposed technique is shown to be accurate, efficient and robust. Abstract: Vehicle frequency and pavement roughness are two factors that used to adversely affect the vehicle scanning method for bridges. To tackle these at once, this study proposes the use of a novel frequency-free test vehicle in parked state for bridge measurement. In terms of measurement speed and data quality, the proposed technique is a trade-off between the moving vehicle and fixed sensor techniques, which has the advantage of movability. A test vehicle (single-axle) is considered frequency-free if its frequency is made far larger than those of the bridge of interest. The test vehicle will also be free of pavement roughness if it is used in the parked (non-moving) state. Firstly, based on the bridge-vehicle transmissibility, a test vehicle is designed to have a frequency far beyond those of the bridge of concern, thereby enhancing the bridge frequency peaks. Secondly, lab tests were conducted for two axle-wheel assemblies under ambient vibration. Of interest is that the axle with PU tires shows a favorable random, small and even spectral distribution with no self frequency up to 20 Hz. The PU tires was then assembled as a part of the test vehicle that is self balanced in entity. Finally, the self-made test vehicle was calibrated on a benchmarked bridge and applied to the Xiamen Bus Rapid Transit system. Taking a three-span girder bridge of the system as an example, it was demonstrated that the frequencies, mode shapes and damping ratios of the first four modes of the bridge (flexural or torsional) can be well detected by the frequency-free test vehicle. Compared with the direct measurement, the proposed technique is equally accurate, but more competitive in efficiency and movability .